AB0174 Muscle wasting in HTNFTG mice; an animal model for rheumatoid arthritis; due to increased cathepsin l expression. (23rd January 2014) - Willburger, M.; Niederreiter, B.; Jelinek, A.; Shvets, T.; Smolen, J.; Redlich, K.; Hayer, S.
Abstract : Objectives: To investigate the impact of systemic inflammation on skeletal muscles in human tumor necrosis factor transgenic (hTNFtg) animals. Methods: We isolated triceps surae, as well as rectus abdominis muscles from hTNFtg animals at different time-points of disease starting at week 4 after birth. Muscle weight and body weight were assessed from these animals. Age and sex-matched wildtype (wt) animals served as controls. Moreover, hTNFtg animals were treated with anti-TNF ab (Infliximab, 10mg/kg, 3x per week, i.p.) and we performed quantitative real-time PCR for Cathepsin L, B, S, H, D, LC3-B, MMP-9 and Interleukin (IL)-1 and IL-6 from mRNA isolated from muscle tissues of hTNFtg and wt animals. Muscle tissue sections were also stained for macrophages, neutrophils, T cells and B cells. Results: We could demonstrate that hTNFtg mice significantly lost muscle weight when compared to sex- and age matched wt animals. Reductions in muscle weight became already manifest at early stages of the disease, at week 4, and continuously progressed until week 16. Due to decreased muscle weight, bodyweight was also significantly lower in hTNFtg animals compared to their wt littermates. We also found significantly increased mRNA expression levels of Cathepsin L, a lysosomal endopeptidase responsible for muscle protein degradation, in muscles from hTNFtg compared to their wt littermates. In contrast, other proteases such as cathepsin B, S, H, D did not significantly increased differ between these 2 genotypes. In addition, we also found LC3B, an enzyme for autophagy-lysosome-mediated proteolysis, to be upregulated in hTNFtg mice compared to wt animals. Moreover, proinflammatory cytokines such as IL-1 and IL-6 were also significantly upregulated in muscles from hTNFtg mice. Interestingly, we observed an increased presence of macrophages and granulocytes in the muscle vascular system but no accumulation of inflammatory cells into the muscle tissue. To evaluate whether the observed changes in muscular tissue are a result of local inflammation or of systemic nature we also investigated the rectus abdominis muscle which is not located between inflamed articular joints. We found elevated levels of Cathepsin L and LC3B in this muscle, indicating that hTNFtg mice suffer from a systemic muscle proteolysis due to systemic inflammation. Conclusions: Despite spontaneous development of chronic inflamed, erosive arthritis, chronic overexpression of TNF leads to skeletal muscle atrophy due to increased tissue-degrading cathepsin L in hTNFtg animals. Disclosure of Interest: None Declared